Stability Testing Occurred On Piroxicam Cream Preparation By Using Stearic Acid And Triethanolamine As Emulsifying Agents - Aldila, Silvy; Girsang, Valentina; Rahmawati, Ina Sonia; Maharai, Daniel; Sa’adah, Anifatus (Science and Community Pharmacy Journal, 2023)
Preface: Piroxicam is classified as a Class 2 product in the Biopharmaceutic Classification System due to its limited solubility in water. The cream preparations underwent optimisation of the stearic acid and triethanolamine concentrations. The optimisation results indicate that the most favourable amounts of stearic acid and triethanolamine (TEA) are 16% and 4% respectively. The physical attributes test yielded positive findings for the formula, indicating a successful cream formulation that satisfied the specified criteria. Purpose: The cream formulation is thereafter submitted to a stability assessment. The purpose of the stability test is to ascertain the long-lasting quality of the preparation when subjected to various storage circumstances. Procedure: Stability tests were conducted over 6 cycles at temperatures of 4° C and 40° C. During the testing phase, various characteristics of the cream preparation were assessed, including organoleptic properties, homogeneity, viscosity, adhesive power, spreadability, and pH. Result: The formulated solution successfully fulfils the criteria of the physical characteristics test, with the following parameter values: pH of 6.8, viscosity of 11010 Cps, spreading power of 6.8 cm, adhesive power of 2.6 seconds, and protective power of 6.5 seconds. Conclusion: The t-test findings conducted before and after assessing the stability of the preparation indicated a p-value greater than 0.05, indicating the absence of a significant difference.